Amphibians and reptiles of Ica department, with comments on their distributions - Mendoza, Alejandro (2023)
This paper presents the updated list of amphibians and reptiles of Ica. Species are commented, accompanied by distribution maps and identification keys for reptiles and amphibians. Information was collected from scientific collections, scientific articles, governmental wildlife agency reports, and specialized taxonomic database. Additionally, between 2019 and 2020, field surveys were carried out in areas with information gaps. A total of 22 species were found (amphibians 3 and reptiles 19). The new records of reptiles include the Liolaemus evaristoi lizard and the Incaspis tachymenoides snake from Chincha province at 4200 and 3200 m altitude respectively, the Stenocercus ornatissimus lizard and the blind snake Epictia tesselata from Pisco province at 3500 and 2800 m respectively. New amphibian records include Pleurodema marmoratum in Chincha province (3900 m) and Telmatobius rimac in Chincha and Palpa provinces at 3900 and 2350 m respectively. The greatest richness and local endemism were found in the coastal desert, while the expansion of distribution and regional endemism were recorded on the western slope of the Andes. Also, it is observed that the families Leptotyphlopidae and Viperidae, and the genera Dicrodon, Stenocercus and Oxyrophus are finishing their distribution in the western slope and the coastal zone of the departments of Ica and Arequipa without representatives in the extreme south of Peru and north of Chile.